2014
DOI: 10.2337/dc13-1995
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Determinants of Progression of Type 2 Diabetes: A DIRECT Study

Abstract: OBJECTIVETo identify the clinical and genetic factors that explain why the rate of diabetes progression is highly variable between idividuals following diagnosis of type 2 diabetes. RESEARCH DESIGN AND METHODSWe studied 5,250 patients with type 2 diabetes using comprehensive electronic medical records in Tayside, Scotland, from 1992 onward. We investigated the association of clinical, biochemical, and genetic factors with the risk of progression of type 2 diabetes from diagnosis to the requirement of insulin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
99
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 23 publications
19
99
5
Order By: Relevance
“…Our findings are in accordance with other studies that have reported the association between younger age at diagnosis and faster progression of diabetes [1,[4][5][6][7][8]. Individuals diagnosed younger than 50 years of age progress rapidly compared with individuals diagnosed over the age of 70 (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our findings are in accordance with other studies that have reported the association between younger age at diagnosis and faster progression of diabetes [1,[4][5][6][7][8]. Individuals diagnosed younger than 50 years of age progress rapidly compared with individuals diagnosed over the age of 70 (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…We have previously reported that earlier calendar year of diagnosis is associated with risk of progression, as defined by requirement for insulin treatment [6]. We believe that this reflects a change in practice over time, with possibly two factors influencing progression rate.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Stratification of patients by risk, comorbidities, patient experience, and diagnosis is therefore a key part of informing effective care [72, 73] and determines the context for care.…”
Section: Resultsmentioning
confidence: 99%